Human monoclonal antibody for ovarian clear cell carcinoma-2, a human monoclonal antibody with antitumor activity against ovarian cancer cells that recognizes CA125-like antigen. Issue 5 (1st August 2008) - Suzuki, N.; Tamada, Y.; Shigirahara, K.; Suzuki, A.; Susumu, N.; Ishida, I.; Aoki, D.
Abstract : In recent years, antibody therapy employing monoclonal antibodies has become a new approach for treating cancer. This study was performed to establish a human monoclonal antibody recognizing an epitope related to CA125 using KM mice and to assess its reactivity with ovarian cancer cells. A human ovarian clear cell adenocarcinoma cell line (RMG-I) was used to immunize KM mice, and hybridoma supernatant was obtained by a standard method employing enzyme-linked immunosorbent assay screening. Next, selection of hybridomas was performed with two antibodies (MA602-1 and MA602-6) and a sandwich immunoassay for CA125-like antigen, and then the limiting dilution was used to obtain a human monoclonal antibody. Immunohistochemical reactivity of this antibody (human monoclonal antibody for ovarian clear cell carcinoma-2 [HMOCC-2]) with ovarian cancer was assessed, while its specificity was analyzed by Western blotting. Various antibodies were used to identify the epitope targeted by HMOCC-2. Finally, the antitumor effect of HMOCC-2 was assessed by intraperitoneal administration to SCID (severe combined immunodeficiency) mice with heterografts of RMG-I tumors. HMOCC-2 showed a positive reaction with 60% (63/105) of ovarian cancer specimens. Western blotting of the membrane fraction of RMG-I revealed several bands at 120–250 kd. HMOCC-2 recognized the CA125-like antigens identified by several antibodies. HMOCC-2 also exhibited significant antitumor activity ( P < 0.01) against ovarian cancer heterografts. HMOCC-2 reacts specifically with ovarian cancer cells via a target epitope analogous to that of CA125 and also exhibits activity against ovarian tumors. These findings suggest that it may have the potential to be employed clinically for molecular-targeting therapy.